Common-pool community resource use: Governance and management of community irrigation schemes in rural Ghana. Issue 1 (1st January 2022) - Ziem Bonye, Samuel; Yenglier Yiridomoh, Gordon; Der Bebelleh, Frederick
ABSTRACT: The Hardian solutions to the excessive abuses of common-pool resources are still being contested. However, studies on governance and management of community irrigation facilities as a "common" in developing countries is limited. Contributing to literature on irrigation water management in the Global South, this paper examines the role of communities in the governance and management of small-scale irrigation dams in the Upper East Region of Ghana. The study employs a qualitative approach to research with 25 interviews and seven Focus Group Discussions (FGDs). Using a thematic approach to analysis, the study reveals that smallholder farmers through the Water Users' Associations (WUAs) have defined user boundaries and instituted ground rules and regulations to enable them to sustainably manage these water resources for their activities of agriculture. Further results revealed that irrigable land for dry season gardening was equitably shared among farmers who are members of WUA, and as a result, minimized possible conflicts among the resource users. The study recommends the need for the Ministry of Food and Agriculture and the Ghana Irrigation Authority to provide more technical support to WUAs in the Upper East Region of Ghana to enable them to better manage these water resources.